Untargeted toxicology in sudden cardiac arrest victims. (19th May 2022) - Stampe, NK; Glinge, C; Rasmussen, BS; Bhardwaj, P; Linnet, K; Jabbari, R; Hassager, C; Kjaergaard, J; Tfelt-Hansen, J; Winkel, BG
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Union's Horizon 2020 research and innovation programme to J.T.-H under acronym ESCAPE-NET Background: Sudden cardiac arrest (SCA) is a major public health challenge and is associated with poor outcomes. Many drugs are known to increase risk of arrythmias and ultimately sudden cardiac death. To our knowledge an untargeted toxicological analysis has not previously been performed in an initially resuscitated SCA cohort. Purpose: We aimed to determine the qualitative and quantitative drug composition present in SCA patients by using forensic toxicological analytical chemistry of all illicit, non-prescription and prescribed drugs, and further investigate whether these drugs are in therapeutic levels or overdosed and to correlate the clinical findings with the toxicology results. Methods: We performed a prospective single-tertiary-center study and included all SCA victims (aged 18-90 years) admitted to our cardiac intensive care unit, between February 2019 to November 2019 (Figure 1). Traumatic and overt overdose related SCA were not included in the study. Drugs used during resuscitation and administered prior to sample collection were identified in each patient and excluded. Results: We prospectively identified 85 all-cause SCA patients with a median age of 60 years (IQR: 53-71) and male predominance (80%). The majority had a shockable rhythm as first rhythm (95%). The major cause of cardiac arrest was acute and chronic ischemia (56/77, 66%), followed by cardiomyopathy (9/77, 12%), idiopathic ventricular fibrillation (8/77, 10%), bradycardia (2/77, 2.6%), primary arrhythmia (1/77, 1.3%), other (1/77, 1.3%). The remaining 8 patients (9.4%) died prior to diagnosis. A positive toxicology was identified in 67 patients (79%) with a total of 218 detected drugs. The most frequent drugs were mild analgesics (32/85, 38%), beta-blockers (21/85, 25%) and ACE-inhibitors/ARB (20/85, 24%). A total of 9 (11%) patients had one or more potentially abusable drugs detected, with the most common being opioid agonists in 5 patients (Figure 2). Importantly, all drugs were found at sub-therapeutic or therapeutic concentrations. None had overdose concentrations. Moreover, polypharmacy was common and a median of 2 drugs (IQR: 1-4) were detected (excluding caffeine that was detected in 83 patients). Conclusion: We found that the majority had drugs detected, and polypharmacy is displayed in a considerable proportion. Potentially abusive drugs were encountered in 11%. However, we did not identify any occult overdose related cardiac arrests among all resuscitated SCA patients. In our setting, toxicological screening in cardiac arrest patients who is not obviously overdosed is excessive.